Multitopic 3, 2′:6′, 3′′-terpyridine ligands as 4-connecting nodes in two-dimensional 4, 4-networks. Issue 40 (28th September 2022) - Manfroni, Giacomo; Spingler, Bernhard; Prescimone, Alessandro; Constable, Edwin C.; Housecroft, Catherine E.
Abstract : Ligands containing two 3, 2′:6′, 3′′-terpyridine metal-binding domains act as 4-connecting nodes in 2D (4, 4)-networks; subtle structural changes occur on coordination to Cu(ii ) or Zn(ii ). Abstract : The tetratopic 1, 4-bis(2-phenylethoxy)-2, 5-bis(3, 2′:6′, 3′′-terpyridin-4′-yl)benzene (1 ) and 1, 4-bis(3-phenylpropoxy)-2, 5-bis(3, 2′:6′, 3′′-terpyridin-4′-yl)benzene (2 ) ligands have been prepared and fully characterised. Combination of ligand 1 or 2 and [M(hfacac)2 ]· x H2 O (M = Cu, x = 1; M = Zn, x = 2) under conditions of crystal growth by layering led to the formation of [Cu2 (hfacac)4 (1 )] n ·3.6 n (1, 2-Cl2 C6 H4 )·2 n CHCl3, [Zn2 (hfacac)4 (1 )] n · n MeC6 H5 ·1.8 n CHCl3, [Cu2 (hfacac)4 (2 )] n · n MeC6 H5 ·2 n H2 O, [Cu2 (hfacac)4 (2 )] n ·2.8 n C6 H5 Cl and [Cu2 (hfacac)4 (2 )] n ·2 n (1, 2-Cl2 C6 H4 )·0.4 n CHCl3 ·0.5 n H2 O. For each compound, single-crystal X-ray analysis revealed the assembly of a planar (4, 4)-net in which the tetratopic ligands 1 or 2 define the nodes. The metal centres link two different bis(3, 2′:6′, 3′′-tpy) ligands via the outer pyridine rings; whereas copper(ii ) has N-donors in a trans -arrangement, zinc(ii ) has them in cis . This difference between the copper(ii ) and zinc(ii ) coordination polymers modifies the architecture of the assembly without changing the underlying (4, 4)-network.